Função social da propriedade intelectual: compartilhamento de arquivos e direitos autorais na CF/88 - Mizukami, Pedro Nicoletti (2007)
Noticing that debates concerning the constitutional aspects of copyright are either rare or insufficient in Brazilian legal literature especially when it comes to dealing with themes regarding the current crisis of intellectual property rights we sought out to investigate which answers could be found in the Brazilian Constitution for the problem of file sharing. Starting out from the hypothesis that adequate solutions could be found by understanding the meaning and the extent of the social function of property clause established under art. 5º, XXIII of the Constitution, we adopted Lawrence Lessig s model of four modalities of constraint to frame an interdisciplinary approach to the problem. We chose not to ignore legal dogmatics, but to deal with it in a theoretical environment that prioritizes policy considerations, with the goal of developing an optimal regime of copyright exceptions. We conclude that there is room for an interpretation of the Brazilian Constitution under which file sharing would be legal, along with other practices that are currently considered to constitute copyright infringement. On the other hand, we also conclude that any reasonable interpretation of the Brazilian Constitution would disallow maximalist implementations of copyright law, and that the copyright exception regime established by the Brazilian Copyright Statute (Lei n.º 9.610/98) is not wide enough to meet the demands of the social function of intellectual property, as required by the Constitution. If construed restrictively, the Brazilian Copyright Statute is unconstitutional as far as exceptions are concerned. The theoretical framework that guided our interpretation of the Constitution is based on a Kelsenian approach on a metatheoretical level, under which two different approaches were used on a theoretical level, applied separately and not together, and with different methodological consequences: Friedrich Müller s Strukturiende Rechtslehre and Robert Alexy s theory of fundamental rights